2019
DOI: 10.1186/s12906-019-2530-8
|View full text |Cite
|
Sign up to set email alerts
|

Online yoga in myeloproliferative neoplasm patients: results of a randomized pilot trial to inform future research

Abstract: Background Myeloproliferative neoplasm (MPN) patients suffer from significant symptoms, inflammation and reduced quality of life. Yoga improves these outcomes in other cancers, but this hasn’t been demonstrated in MPNs. The purpose of this study was to: (1) explore the limited efficacy (does the program show promise of success) of a 12-week online yoga intervention among MPN patients on symptom burden and quality of life and (2) determine feasibility (practicality: to what extent a measure can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(132 citation statements)
references
References 35 publications
2
114
0
Order By: Relevance
“…After removal of duplicate studies and exclusion during the title and abstract level review, 46 full texts remained. Following application of the eligibility criteria, 26 articles were eligible for inclusion 44–68 . Reasons for exclusion of the other 21 articles is presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicate studies and exclusion during the title and abstract level review, 46 full texts remained. Following application of the eligibility criteria, 26 articles were eligible for inclusion 44–68 . Reasons for exclusion of the other 21 articles is presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies were conducted in participants diagnosed with breast cancer (the study by Culos‐Reed et al. was primarily in breast and therefore included in this group), 45,47,49–53,56–59,62–68 two studies in mixed cancers, 46,69 and one study each in the following cancers: colorectal, 55 lymphoma, 54 thoracic, 61 head and neck, 44 myeloproliferative neoplasms 48 and glioma 60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible mechanism could be due to the influence of increased adiposity in the bone marrow which leads to enhanced megakaryocyte maturation and accelerated proplatelet formation in mice [80]. Interventions using yoga in MPN have been performed [81,82], however no interventional studies using more rigorous physical activity with the intent of weight reduction in MPN have been performed.…”
Section: Obesity and Physical Activitymentioning
confidence: 99%
“…Two were systematic reviews [ 21 , 22 ], six were clinical trials [ 23 28 ], and one was an observational study [ 29 ]. While these articles concluded that integrative oncology therapies, such as mind-body and behavioral therapies [ 22 , 23 , 25 28 ], yoga [ 24 ], and exercise [ 21 ], could be feasibly offered in a virtual format and positively affect physical and psychosocial well-being, symptom management, and overall quality of life, limited pragmatic recommendations were provided regarding how to address the unique challenges of online integrative consultations/treatment. The studies examining the feasibility of online interventions provided the most useful suggestions, including the need to maintain the confidentiality of online group sessions, provide initial and on-going technical support, and address slow Internet access and limited technological knowledge [ 25 28 ].…”
Section: Methodsmentioning
confidence: 99%